Eficiência de fontes fosfatadas aplicadas a lanço e em linha na cultura da soja manejada sob semeadura direta - Hansel, Fernando Dubou (2013)
The sources of soluble phosphate fertilizers present differences in their chemical and structural composition coming from the increasing production and consumption demand in the last decades. The product of the reactions between fertilizer and soil, resulting from the composition of phosphate fertilizers, are different, influenced by soil‟s chemical and textural characteristics. With the popularization of the no-till system and intensification of the superficial management, the type of application of phosphate fertilizer also arises as a factor that can interfere in the efficiency of fertilization. In this study the agronomic efficiency of different phosphate sources was evaluated for solubility and application by broadcasting and banding with sowing under no- till. The study was done at the city of São Vicente do Sul, on a sandy loam soil, under no-till on a soybean crop. The treatments were composed by soluble fertilizer sources, with different solubility coefficient, classified by the calcium content in the formulation and by the molecular structure of the sources, in solubility levels (factor A), submitted to different types of application (factor B). Factor A was composed by the sources: 09-45-00 + (7,0 % S0 + 2,0 % SO4) and monoammonium phosphate (MAP) (high solubility), 08-40-00 + (6,6 % S0 + 1,4 % SO4) + 3,4 % Ca and 07-37-06 + (5,2 % S0 + 1,2 % SO4) + 1,4 % Ca (medium solubility), 0-20-20 + (4,6 % SO4)+ 9,9 % Ca, 02-20-18 + (4,6 % SO4) + 9,9 % Ca (low solubility), the doses being adjusted so as to be maintained the same nutritional relation of 92 kg ha-1 for P2O5 and K2O. The different types of application (factor B) were on surface (broadcast), and in the seed row (banding), as the banding was done mechanically. The studied variables were: dry mass production, plant nutrition (foliar method) and grain productivity. The results indicate significant interaction between the factor A and B for grain productivity, dry mass, and absorption of nitrogen, potassium, calcium and magnesium, at the level of significance 5 %. The fertilizer sources that were considered to have high solubility presented higher productivity in average among the levels, as broadcast showed greater agronomic efficiency.